PENGARUH KONSENTRASI PENAMBAHAN TEPUNG TEMPE TERHADAP KARAKTERISTIK TORTILLA LABU KUNING (The Effect of Tempe Flour Addition Concentration on Pumpkin Tortilla Characteristics) - Merynda Indriyani Syafutri; Eka Lidiasari (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2014)
The objective of this research was to observe the physical and chemical characteristics of pumpkin tortilla with tempe flour addition. The experiment was designed using non Factorial Randomized Design with six treatments and each treatment was replicated three times. The treatments were 5%, 10%, 15%, 20%, 25% and 30% addition of tempe flour per 90 g of tapioca. Texture, moisture content, ash content, and protein content were analyzed. The results showed that the addition of tempe flour had significant effect on protein content. Pumpkin tortilla with tempe flour addition had 830.70 mm/s to 1316 mm/s of texture, 3.97% to 4.92% of moisture content, 1.22% to 1.48% of ash content, and 8.96% to 13.22% of protein content. Keywords : pumpkin, tempe flour, tortilla